Exploiting the hopping parameter expansion in the hybrid Monte Carlo simulation of lattice QCD with two degenerate flavors of Wilson fermions - Hasenbusch, Martin (Physical review, 2018)
We show how the hopping parameter expansion at order κ2 and κ4 can be exploited in the simulation of lattice QCD with two flavors of degenerate Wilson fermions. A natural extension of this idea is a “UV filtering” by using rooted polynomials. These approaches can be easily combined with, for example, mass preconditioning. First numerical tests are performed for the Wilson gauge action at β=5.6 and κ=0.156 and 0.1575.
Gesehen am 30.06.2022